Knowledge and Attitude of Hill Farmers towards Improved Agricultural Practices (Indian Journal of Extension Education, 2012)
Green revolution in India has bypassed the remote places like hills. Farmers are struggling for survival under unfavourable conditions like hills requiring attention of scientists. The present study was conducted in Uttarkashi district of Uttarakhand with 120 respondents, selected from 12 villages, using random sampling technique. The results of the study revealed that majority of the respondents had high attitude and medium level of knowledge towards improved agricultural practices. The factors like caste, education, land holding, farming experience, sources of information utilization, annual income, scientific orientation and economic motivation had significant relationship with knowledge and attitude of the respondents. If these factors are taken care of by implementing agencies of the extension programmes, it would certainly increase the adoption rate of improved agricultural technology in hills. Selective exposure of the mass media may help in shaping their attitude in desired direction.